2013
DOI: 10.1186/1471-2407-13-65
|View full text |Cite
|
Sign up to set email alerts
|

MYBBP1A suppresses breast cancer tumorigenesis by enhancing the p53 dependent anoikis

Abstract: BackgroundTumor suppressor p53 is mutated in a wide variety of human cancers and plays a critical role in anoikis, which is essential for preventing tumorigenesis. Recently, we found that a nucleolar protein, Myb-binding protein 1a (MYBBP1A), was involved in p53 activation. However, the function of MYBBP1A in cancer prevention has not been elucidated.MethodsRelationships between MYBBP1A expression levels and breast cancer progression were examined using patient microarray databases and tissue microarrays. Colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 45 publications
4
24
0
Order By: Relevance
“…1B) and anti-p53 co-IP-s (data not shown). It was previously reported, that MYBBP1A physically interacts with p53 [1]. The interaction of MYBBP1A with CDK2 was further confirmed by co-IP of MYBBP1A with anti-CDK2 antibody using nuclear extract prepared from HEK293 cells overexpressing highact TPPII (Fig.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…1B) and anti-p53 co-IP-s (data not shown). It was previously reported, that MYBBP1A physically interacts with p53 [1]. The interaction of MYBBP1A with CDK2 was further confirmed by co-IP of MYBBP1A with anti-CDK2 antibody using nuclear extract prepared from HEK293 cells overexpressing highact TPPII (Fig.…”
Section: Resultssupporting
confidence: 64%
“…p21 [1] p21F primer: 5 0 -GGAGACTCTCAGGGTCGAAA-3 0 and p21R primer: 5 0 -TTAGGGCTTCCTCTTGGAGA-3 0 (200 nM each); 95°C for 2 min, 40 cycles of 10 s at 95°C and 15 s at 57°C.…”
Section: Mybbp1a [27]mentioning
confidence: 99%
“…TPPII functions downstream of the UPS and it may fulfill double role in the proteolysis and in other cellular functions mediated through protein-protein interactions. The p53 regulation on the transcription level may also be affected through the interaction of TPPII with MYBBP1A [13], which binds to p53 and enhances its transcription [28]. The present study confirmed interactions of TPPII with p53 both in the cytoplasmic and the nuclear subcellular compartments.…”
Section: Discussionsupporting
confidence: 81%
“…On the cellular level, the model mice showed functional links between TPPII, p53, and NF-jB [8] presented by increasing of p53 expression and the level of NF-jB in T-cells and by decreasing of NF-jB in fibroblasts. The transcription factor NFjB was found to be co-repressed by MYBBP1A [32], which directly interacted with both TPPII and p53 via protein-protein interactions [13,28]. Interestingly, MYBBP1A inhibited apoptosis through an activation of several antiapoptotic factors e.g.…”
Section: Discussionmentioning
confidence: 99%
“…MYBBP1A can bind to p53 and enhance the transcription of p53 target genes (35,36), and its inhibition significantly enhanced tumorigenesis (35). MYBBP1A can also interact with NF-kB and inhibit NF-kB-dependent transcription (36).…”
Section: Discussionmentioning
confidence: 99%